Simultaneous Determination of Caffeine, Preservatives and Antioxidants in Energy- and Soft-Drinks Commercially Available in Bangladesh - Islam, Md Samiul; Hossain, Md Shahadat; Bhadra, Subrata; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2016)
This study describes a validated assay method to determine caffeine, benzoic acid, methylparaben, propylparaben, butylparaben, butylatedhydroxyanisole, and butylatedhydroxytoluene simultaneously by reversed phase high performance liquid chromatographic (HPLC) method. The separation of compounds was achieved on a C18 column in a gradient of acetonitrile and diluted sulfuric acid (pH=2.3) and quantification was performed by using a UV-detector set at 265 nm. The method was found to be linear over the concentration range of 60-90 ppm (R2=0.995), 200-300 ppm (R2=0.993), 16-24 ppm (R2=0.990), 16-24 ppm (R2=0.994), 16-24 ppm (R2=0.997), 48-72 ppm (R2=0.993), and 32-48 ppm (R2=0.994) for caffeine, benzoic acid, methylparaben, propylparaben, butylparaben, butylatedhydroxyanisole, and butylatedhydroxytoluene, respectively. Sixty energy- and soft-drink samples were analyzed where about 53% were found to contain caffeine among which 16% exceeded the tolerance limit (>200 ppm) set by USFDA. Moreover, 65% of analyzed samples contained benzoic acid and 10% of those samples exceeded the maximum allowable limit (>600 ppm) set by joint expert committee for food additives (JECFA). Dhaka Univ. J. Pharm. Sci. 15(1): 97-108, 2016 (June)